(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article presents an analysis of experimental work on the application of technology based on the use of hatha yoga tools. The scientific expediency of including complexes of yoga exercises in the educational process of physical education in a secondary school is shown